A Proof-of-Concept for Parameter Manipulation in TRIZ: Automotive Case Study - Altun, Koray (My University, 2025)
This paper provides a proof-of-concept for using the Theory of Inventive Problem Solving (TRIZ) methodologies, focusing on parameter deployment and manipulation to solve physical contradictions in automotive seat design. While parameter deployment has been explored in theory, practical applications remain limited, and its potential has not been widely demonstrated. This study addresses this gap by showing how it can resolve the conflict between comfort during normal driving and safety during collisions. Two strategies are introduced: the Transfer-Oriented Approach (TOA) uses a single air bladder system to adjust seat firmness dynamically, ensuring comfort in regular driving and firmness during crashes. The Transfer-Oriented Ap-proach with Adjustment (TOAA) extends this by combining air bladder systems for comfort and shape memory materials for safety, allowing both to work independently. These methods are innovative because they move beyond classical TRIZ principles by integrating external components, achieving dual functionality without compromising performance. This paper contributes to TRIZ literature by providing a practical example of how parameter deployment can be applied in automotive design. It also serves as a guide for engineers and researchers interest-ed in using TRIZ to tackle similar design challenges. By validating the feasibility of this approach, the study opens up possibilities for exploring its use in other areas of automotive design such as climate control systems or crash energy management. The findings highlight how systematic innovation can transform theoretical methods into real-world solutions, offering practical insights for future applications within the automotive industry.
Keywords: Automotive seat design; Parameter transfer; TRIZ - Theory of inventive problem solving